Determinants of China's bank profitability under the LPR policy - Wu, Yifan (2022)
This paper studies the profitability of 30 Chinese banks from 2011 to 2020. The classification model is used to analyze the data of nation-owned banks, joint-stock commercial banks and urban commercial banks, so as to explore the factors affecting the profitability of Chinese banks under the LPR policy. In addition, this paper also provides some suggestions for the future development of Bank of China.